The key role of clean energy and technology in smart cities development. (November 2022) - Razmjoo, Armin; Gandomi, Amir H.; Pazhoohesh, Mehdi; Mirjalili, Seyedali; Rezaei, Mostafa
Abstract: Humanity is currently facing immense challenges related to the reduction of CO2 emissions and satisfying energy demand whilst mitigating environmental impacts, hence, developing smart cities is one of the most important goals for every country. This paper presents a comprehensive discussion on smart city development across successful cities including London, Singapore, Barcelona, New York, Melbourne, Amsterdam, Dubai, and Helsinki, highlighting the importance of appropriate policies in overcoming barriers and creating solutions with regard to the importance of clean energy in each section. This paper focuses on three sectors: Energy, Transport, and Buildings. This research aims to illustrate fruitful pathways for smart city development based on these successful cities in using appropriate policies and strategies to overcome the relative hurdles often limiting these three important sectors in improving and achieving the necessary development for smart city status. Additionally, the stakeholder cooperation with the local government has a prominent role in carrying and executing the ideas of the politicians and the energy experts for more utilization of clean energy in different sections as a proper policy in smart city development. Highlights: Conceptual consideration of the role of clean energy on smart cities development. Investigation the role of clean energy on Transportation, buildings and energy systems. Investigation strategies and policies of the successful smart cities. Investigation the role of technologies on clean energy development for smart cities.